Kesadaran Masyarakat Terhadap Pelaksanaan Nikah Pada Masa Pandemi Covid-19 - Sukma Ayu Lestari (Jurnal El-Thawalib, 2022)
The focus of this research is marriage services during the Covid-19 Pandemic to the people of Southeast Padangsidimpuan District, Padang Sidempuan City, by raising two main problems, namely 1) how is the implementation of marriage during the Covid-19 Pandemic in Southeast Padangsidimpuan District? 2) How is the awareness of the people of Southeast Padangsidimpuan District towards Circular No: P-006/DJ.III/Hk.00.7/06/2020 Regarding Marriage Services in the Covid-19 Era?. The approach used in this study is a qualitative-descriptive approach, namely data collection by means of interviews, observations and document studies. The results showed that most of the people already knew about the rules of service during the Covid-19 Pandemic, but because according to them marriage is a history that only happens once in a lifetime and is also a sacred thing in life so they don't care about the rules that apply. there is already the most important thing is to stick to the prokes during the wedding. But on the other hand, there are also some people who don't know about marriage rules during the Pandemic, but they know that during the pandemic it's not allowed to gather a lot of people. So the results of this study indicate that there is no public awareness of the Southeast Padangsidimpuan District towards marriage services during the Covid-19 Pandemic.